Evaluating the Effect of Superdosing Natuphos E 5,000 G Phytase on Nursery Pig Performance - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 360 nursery pigs (DNA 200 × 400, initially 12.92 lb) were used in a 42-d growth trial to determine the effect of superdosing a novel phytase source (Natuphos E 5000 G, BASF Corporation, Florham Park, NJ). Pigs were randomly allotted to pens at weaning in a randomized complete block design to 1 of 8 dietary treatments. There were 5 pigs per pen and 9 pens per treatment. Diets were fed in 3 phases from d 0 to 7, 7 to 21, and 21 to 42. Dietary treatments were a negative control (NC) with 0.40, 0.30, or 0.25% aP from inorganic P for Phases 1, 2, and 3, respectively; and the NC with increasing phytase levels of 500, 1,000, 2,000, 3,000, or 4,000 phytase units (FTU)/kg. There was also a positive control (PC) with 0.55, 0.45, or 0.40% aP from inorganic P for Phases 1, 2, and 3, respectively, or the PC with 2,000 FTU/kg. On d 42, one pig per pen was euthanized and the right fibula was removed for bone ash analysis. From d 0 to 42, pigs fed increasing phytase in the negative control diet tended to have increased (quadratic, P = 0.064) ADG resulting in heavier (linear, P = 0.082) ending BW and improved (quadratic, P<0.01) F/G. Adding 2,000 FTU/kg phytase to the positive control diet did not influence ADG or ADFI, but tended to improve (linear, P = 0.068) F/G. The NC diet with 500 FTU/kg and PC diets were formulated to be equivalent in available Ca and P. When comparing the two diets, pigs fed the positive control diet had increased (linear, P = 0.007) ADFI; however, pigs fed the NC with 500 FTU/kg phytase diets had improved (linear, P = 0.034) F/G. Bone ash weights were increased (quadratic, P<0.001) for pigs fed increasing phytase in the NC diets. Additionally, percentage bone ash values increased as phytase increased in the NC (linear, P<0.001) and PC (P<0.001) diets. There was a tendency for the PC diet to have greater (P = 0.099) percentage bone ash when compared to the NC diet with 500 FTU/kg of phytase. In summary, this study shows that increasing dietary phytase increased percentage bone ash values, and a tendency for improved F/G as phytase was added to the positive control diet with P and Ca formulated at NRC (2012) recommendations. However, there was no further improvement in growth performance when phytase was included above 1,000 FTU/kg.
Keywords: nursery pig; phosphorus; phytase; superdose